PRICE FLUCTUATION AND SPATIAL MARKET INTEGRATION OF RICE IN ADAMAWA STATE RICE MARKET (FULafia Journal of Science and Technology, 2019)
This study investigates spatial price transmission for rice in Adamawa state, Nigeria. Data on weekly basis for the prices of 100kg was collected from ten markets for 52 weeks (September 2015 - August 2016). Data were analyzed with an econometric framework based on the estimation of Autoregressive Distributed lags models, and of the corresponding Error correction specification. Test for Granger causality was also performed. The extent of divergence of the lowest price from the highest price over the period of twelve months wasused to examine the dynamics of price behavior of rice marketing. The result of seasonal variation in price revealed that October and November is the period when rice prices are generally low while the highest price month occurred in December.